IMPROVEMENT ALGEBRAIC THINKING ABILITY USING MULTIPLE REPRESENTATION STRATEGY ON REALISTIC MATHEMATICS EDUCATION - Kusumaningsih, Widya; Darhim, Darhim; Herman, Tatang; Turmudi, Turmudi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
The study aimed at improving students’ algebraic thinking ability in the eighth-grade junior high school student through multiple representation strategies using realistic approach. The multiple representation strategies consist of orientation, exploration, internalization, and evaluation. This is a quasi-experimental study with nonrandomized pretest-posttest control group design. The population of this study was the student the eighth grade in Kudus city. Two classes were selected and classified as a class experiment that subject are given multiple representation strategies using realistic approach, and one other class as a control class that subjects are given scientific approach. Data obtained was analyzed by the independent t-test and proportions test. The result showed that there was an interaction between the multiple representation strategies using the realistic approach on the ability of algebraic thinking. The students with multiple representation strategies had better algebraic thinking ability than those with current scientific learning. In addition, more than seventy-five percent of the students with multiple representation strategies using realistic approach fulfill the learning completeness.